Membrane electrode assembly and electric pile of air-cooled fuel cell
By introducing porous materials into the membrane electrode assembly of the air-cooled fuel cell stack, the humidity of the catalytic layer is adjusted, and the problem of uncontrollable humidity in the internal reaction zone of the fuel cell is solved, and the power generation efficiency and oxygen utilization efficiency are improved.
Patent Information
- Application Number
- CN202411550090.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-03-11
AI Technical Summary
The existing air-cooled fuel cell stacks are used together on the cathode side because oxygen supply and heat dissipation are used, resulting in the humidity in the internal reaction zone of the fuel cell that cannot be controlled, affecting the power generation efficiency.
Porous materials are introduced into the cathode catalytic layer of the membrane electrode assembly, and the humidity of the catalytic layer is adjusted through capillary aggregation phenomenon to achieve controllability in the humidity of the reaction area inside the fuel cell.
By adjusting the humidity of the catalytic layer, the power generation efficiency of the fuel cell is improved, and the three-phase reaction interface of the catalytic layer is increased, thereby improving the utilization efficiency of the oxidant oxygen.
Smart Images

Figure BDA0005114839810000061
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hydrogen fuel cells, and in particular to a membrane electrode assembly and a fuel cell stack of an air-cooled fuel cell. Background Art
[0002] A hydrogen fuel cell is a fuel cell that uses hydrogen and air as fuel to generate electricity. It uses a proton exchange membrane as an electrolyte and directly converts the chemical energy of hydrogen and oxygen into electrical energy through an electrochemical reaction. It has the advantages of high energy efficiency, zero emissions, low noise, and reliable continuous load operation. With the growing global demand for sustainable energy and the reduction of greenhouse gas emissions, the application prospects of hydrogen fuel cells in transportation, energy storage, and mobile power sources are widely optimistic. Fuel cells can be divided into air-cooled fuel cells (referred to as air-cooled fuel cells) and liquid-cooled fuel cells according to the cooling method. Because air-cooled fuel cells have the advantages of simple and compact structure and rapid power supply response, they are widely used in backup power supplies, drone power batteries, forklift power batteries, portable power sources and other scenarios.
[0003] A fuel cell stack is a battery group that stacks multiple fuel cell cells in series, and then a current collector for collecting the stack current and an end plate for support are set at each end of the battery group, and an insulating layer is set between the current collector and the end plate. Each single cell mainly consists of a hydrogen flow field plate and an air flow field plate, and a membrane electrode assembly (MEA) sandwiched between the hydrogen flow field plate and the air flow field plate.
[0004] The membrane electrode assembly is the core component of hydrogen fuel cells. It is the place where chemical energy is converted into electrical energy during the operation of the battery, and plays a key role in the performance of hydrogen fuel cells. The membrane electrode is usually composed of a proton exchange membrane and electrodes arranged on both surfaces of the proton exchange membrane. Usually, the electrode includes a catalyst layer and a gas diffusion layer, and the catalyst layer is arranged between the gas diffusion layer and the proton exchange membrane. The electrochemical reaction carried out in the catalyst layer is carried out on a three-phase interface with reaction gas, protons and electrons at the same time. The current mainstream commercial proton exchange membrane is a perfluorosulfonic acid proton exchange membrane with water molecules as the proton conduction medium. Its chemical structure is composed of a hydrophobic polytetrafluoroethylene skeleton and a side chain of a perfluorovinyl ether with a hydrophilic sulfonic acid group (-SO3H) as the terminal group. The water content directly affects the proton conductivity of the proton exchange membrane.
[0005] In an air-cooled fuel cell system, the amount of air required for the electrochemical reaction inside the fuel cell and the temperature stability inside the fuel cell stack are all provided by the fan, so the supply of oxygen to the oxidant gas of each individual fuel cell cannot be controlled individually, resulting in the inability to ensure the humidity of the reaction area inside the fuel cell. Too low or too high humidity will reduce the power generation efficiency of the fuel cell, and even cause damage to the fuel cell in severe cases.
[0006] The technical problem to be solved by the present invention is to overcome the deficiency in the prior art that the oxygen supply and heat dissipation of the air-cooled fuel cell stack share the cathode side, resulting in the inability to control the humidity of the internal reaction zone of the fuel cell, and to provide a solution for the membrane electrode assembly and stack of an air-cooled fuel cell. Summary of the invention
[0007] In view of the problem in the prior art that the oxygen supply and heat dissipation of the air-cooled fuel cell stack share the cathode side, resulting in the uncontrollable humidity of the internal reaction zone of the fuel cell, the present invention specifically relates to a membrane electrode assembly and stack of an air-cooled fuel cell. The membrane electrode assembly is characterized in that a porous material is added to its cathode catalyst layer, which can achieve controllable humidity in the internal reaction zone of the fuel cell. When the humidity of the catalyst layer is too high, capillary condensation can occur in the pores of the material, thereby absorbing excess water and reducing mass transfer resistance; when the humidity of the catalyst layer is too low, the water stored in the pores of the material is released through the pores, thereby increasing the moisture content of the catalyst layer and improving the power generation efficiency of the fuel cell. In addition, due to the introduction of the porous material, the three-phase reaction interface of the catalyst layer is enlarged, which is conducive to improving the utilization efficiency of the oxidant oxygen, and is suitable for working environments with low oxygen content in the air.
[0008] In order to solve the above problems, the present invention adopts the following technical solutions:
[0009] A membrane electrode assembly for an air-cooled fuel cell, the membrane electrode assembly having a seven-in-one structure, is stacked in the order of an anode side gas diffusion layer, an anode side sealing frame, an anode catalyst layer, a perfluorosulfonic acid proton exchange membrane, a cathode catalyst layer, a cathode side sealing frame, and a cathode side gas diffusion layer.
[0010] Furthermore, the thickness of the anode side gas diffusion layer is 250-340 μm, and the anode side gas diffusion layer is a kind of carbon fiber paper or carbon fiber cloth; the thickness of the cathode side gas diffusion layer is 250-340 μm, and the cathode side gas diffusion layer is a kind of carbon fiber paper or carbon fiber cloth; the thickness of the perfluorosulfonic acid proton exchange membrane is 15-25 μm.
[0011] Furthermore, the anode catalyst layer is obtained by uniformly dispersing a perfluorosulfonic acid resin solution and a noble metal catalyst to prepare an anode catalyst slurry, and then coating it on one side of a perfluorosulfonic acid proton exchange membrane by ultrasonic spraying.
[0012] Furthermore, the mass concentration of the perfluorosulfonic acid resin solution is 5-20wt%; the type of the precious metal catalyst is one of a Pt / C catalyst, a PtCo / C catalyst or a PtIr / C catalyst, and the mass ratio of the perfluorosulfonic acid resin solution to the precious metal catalyst is 1-10:1; the content of the precious metal in the anode catalyst layer is 0.1-0.2mg / cm 2.
[0013] Furthermore, the cathode catalyst layer is obtained by uniformly dispersing a perfluorosulfonic acid resin solution, a noble metal catalyst, and a porous material to form a cathode catalyst slurry, and then coating the slurry on the other side of the perfluorosulfonic acid proton exchange membrane by ultrasonic spraying.
[0014] Furthermore, the mass concentration of the perfluorosulfonic acid resin solution is 5-20wt%; the type of the noble metal catalyst is one of Pt / C, PtCo / C or PtNi / C catalysts; the mass ratio of the perfluorosulfonic acid resin solution to the noble metal catalyst is 1-8:1; and the noble metal loading in the cathode catalyst layer is 0.1-0.5mg / cm 2 The porous material is one or a mixture of two or more of porous ceramic materials, metal organic framework materials, mesoporous porous silica, three-dimensional porous carbon nanotubes and polymer porous materials, and the mass of the porous material accounts for 0.7 to 3% of the total mass of the cathode catalyst slurry.
[0015] Furthermore, the thickness of the frame material used for the anode side sealing frame and the cathode side sealing frame is 50-100 μm, and the frame material is one of polyethylene terephthalate PET, polyethylene naphthalate PEN, polyimide PI or polyetherimide PEI.
[0016] A method for preparing a membrane electrode assembly of an air-cooled fuel cell, wherein the membrane electrode assembly is assembled by hot pressing.
[0017] Furthermore, the hot pressing pressure is 10-25 kg / cm 2 , the hot pressing temperature is 80-110℃.
[0018] A stack of an air-cooled fuel cell, the stack being assembled using the membrane electrode assembly of the air-cooled fuel cell mentioned above.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] (1) The present invention realizes controllable humidity in the internal area of the fuel cell by utilizing the structural design of the catalyst layer on the cathode side and the water produced by the electrochemical reaction of hydrogen and oxygen on the cathode side to self-regulate the humidity, thereby alleviating the problem of reduced reaction efficiency of the fuel cell caused by too low or too high humidity; (2) The present invention increases the three-phase reaction interface of the catalyst layer by introducing porous materials, which is beneficial to improving the utilization efficiency of the oxidant oxygen.
[0021] (3) The preparation method of the present invention is simple and efficient, suitable for mass production, and applicable to working environments with low oxygen content in the air. DETAILED DESCRIPTION
[0022] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples.
[0023] Example 1
[0024] S1. A perfluorosulfonic acid resin solution with a mass concentration of 5wt% and a Pt / C catalyst with a Pt content of 50% were uniformly dispersed in a mass ratio of 7:1 to prepare an anode catalyst slurry. The anode catalyst slurry was then coated on one side of a 15μm perfluorosulfonic acid proton exchange membrane by ultrasonic spraying. After drying, a proton exchange membrane with an anode catalyst layer was obtained. The noble metal loading was 0.2mg / cm 2 ;
[0025] S2, a perfluorosulfonic acid resin solution with a mass concentration of 5wt%, a Pt / C catalyst with a Pt content of 60%, and a mesoporous porous silica are uniformly dispersed in a mass ratio of 5:0.95:0.05 to prepare a cathode catalyst slurry, and then the cathode catalyst slurry is coated on the other side of the perfluorosulfonic acid proton exchange membrane with an anode catalyst layer obtained in the above step S1 by ultrasonic spraying, and the cathode catalyst layer is coated after drying to obtain a catalyst coating proton membrane CCM, and the total precious metal loading is 0.5mg / cm 2 ;
[0026] S3. Stack the anode side gas diffusion layer, anode side sealing frame, anode catalyst layer, perfluorosulfonic acid proton exchange membrane, cathode catalyst layer, cathode side sealing frame, and cathode side gas diffusion layer in order, and then prepare a seven-in-one membrane electrode assembly by hot pressing. Among them, the thickness of the anode side gas diffusion layer is 250μm, and the material is carbon fiber cloth; the thickness of the cathode side gas diffusion layer is 250μm, and the material is carbon fiber cloth; the frame material used for the anode side sealing frame is polyethylene terephthalate PET with a thickness of 75μm; the frame material used for the cathode side sealing frame is polyethylene terephthalate PET with a thickness of 75μm; the thickness of the perfluorosulfonic acid proton exchange membrane is 15μm; during the hot pressing assembly process, the hot pressing pressure used is 20kg / cm 2 , the hot pressing temperature is 80℃.
[0027] Example 2
[0028] S1. A perfluorosulfonic acid resin solution with a mass concentration of 5% and a Pt / C catalyst with a Pt content of 60% were uniformly dispersed in a mass ratio of 8.4:1 to prepare an anode catalyst slurry. The anode catalyst slurry was then coated on one side of a 15 μm perfluorosulfonic acid proton exchange membrane by ultrasonic spraying. After drying, a proton exchange membrane with an anode catalyst layer was obtained. The noble metal loading was 0.1 mg / cm 2 ;
[0029] S2, a perfluorosulfonic acid resin solution with a mass concentration of 5%, a PtNi / C catalyst with a Pt content of 50%, and a mesoporous porous silica are uniformly dispersed in a mass ratio of 6:0.98:0.05 to prepare a cathode catalyst slurry, and then the cathode catalyst slurry is coated on the other side of the perfluorosulfonic acid proton exchange membrane with an anode catalyst layer obtained in the above step S1 by ultrasonic spraying. After drying, the cathode catalyst layer is coated to obtain a catalyst coated proton membrane (CCM), and the total precious metal loading is 0.6 mg / cm 2 ;
[0030] S3. Stack the anode side gas diffusion layer, anode side sealing frame, anode catalyst layer, perfluorosulfonic acid proton exchange membrane, cathode catalyst layer, cathode side sealing frame, and cathode side gas diffusion layer in order, and then prepare a seven-in-one membrane electrode assembly by hot pressing. Among them, the thickness of the anode side gas diffusion layer is 320μm, and the material is carbon fiber paper; the thickness of the cathode side gas diffusion layer is 280μm, and the material is carbon fiber paper; the frame material used for the anode side sealing frame is polyethylene naphthalate PEN with a thickness of 50μm; the frame material used for the cathode side sealing frame is polyethylene naphthalate PEN with a thickness of 50μm; the thickness of the perfluorosulfonic acid proton exchange membrane is 15μm; during the hot pressing assembly process, the hot pressing pressure used is 15kg / cm 2 , the hot pressing temperature is 110℃.
[0031] Example 3
[0032] S1. A perfluorosulfonic acid resin solution with a mass concentration of 10% and a Pt / C catalyst with a Pt content of 60% and a PtIr / C catalyst with a mass ratio of 3.5:0.9:0.1 were uniformly dispersed to form an anode catalyst slurry. Then, the anode catalyst slurry was coated on one side of a 15 μm perfluorosulfonic acid proton exchange membrane by ultrasonic direct spraying. After drying, a proton exchange membrane with an anode catalyst layer was obtained. The noble metal loading was 0.3 mg / cm 2 ;
[0033] S2, a perfluorosulfonic acid resin solution with a mass concentration of 10%, a Pt / C catalyst with a Pt content of 60%, and a three-dimensional porous carbon nanotube are uniformly dispersed in a mass ratio of 6:1:0.1 to prepare a cathode catalyst slurry, and then the cathode catalyst slurry is coated on the other side of the proton exchange membrane with the anode catalyst layer obtained in the above step S1 by ultrasonic direct spraying. After drying, the cathode catalyst layer is coated to obtain a catalyst coated proton membrane (CCM), and the total precious metal loading is 0.4 mg / cm 2 ;
[0034] S3. Stack the anode side gas diffusion layer, anode side sealing frame, anode catalyst layer, perfluorosulfonic acid proton exchange membrane, cathode catalyst layer, cathode side sealing frame, and cathode side gas diffusion layer in order, and then prepare a seven-in-one membrane electrode assembly by hot pressing. Among them, the thickness of the anode side gas diffusion layer is 340μm, and the material is carbon fiber paper; the thickness of the cathode side gas diffusion layer is 280μm, and the material is carbon fiber paper; the frame material used for the anode side sealing frame is polyethylene terephthalate PET with a thickness of 100μm; the frame material used for the cathode side sealing frame is polyethylene terephthalate PET with a thickness of 100μm; the thickness of the perfluorosulfonic acid proton exchange membrane is 15μm; during the hot pressing assembly process, the hot pressing pressure used is 10kg / cm 2 , the hot pressing temperature is 80℃.
[0035] Example 4
[0036] S1. A perfluorosulfonic acid resin solution with a mass concentration of 20wt% and a Pt / C catalyst with a Pt content of 40% were uniformly dispersed in a mass ratio of 7:1 to prepare an anode catalyst slurry. The anode catalyst slurry was then coated on one side of a 25μm perfluorosulfonic acid proton exchange membrane by ultrasonic spraying. After drying, a proton exchange membrane with an anode catalyst layer was obtained. The noble metal loading was 0.2mg / cm 2 ;
[0037] S2, a perfluorosulfonic acid resin solution with a mass concentration of 20wt%, a PtCo / C catalyst with a Pt content of 50%, and a three-dimensional porous carbon nanotube are uniformly dispersed in a mass ratio of 2.4:1:0.1 to prepare a cathode catalyst slurry, and then the cathode catalyst slurry is coated on the other side of the perfluorosulfonic acid proton exchange membrane with an anode catalyst layer obtained in the above step S1 by ultrasonic spraying, and the cathode catalyst layer is coated after drying to obtain a catalyst coating proton membrane CCM, and the total precious metal loading is 0.5mg / cm 2 ;
[0038] S3. Stack the anode side gas diffusion layer, anode side sealing frame, anode catalyst layer, perfluorosulfonic acid proton exchange membrane, cathode catalyst layer, cathode side sealing frame, and cathode side gas diffusion layer in order, and then prepare a seven-in-one membrane electrode assembly by hot pressing. Among them, the thickness of the anode side gas diffusion layer is 280μm, and the material is carbon fiber paper; the thickness of the cathode side gas diffusion layer is 280m, and the material is carbon fiber paper; the frame material used for the anode side sealing frame is polyethylene naphthalate PEN with a thickness of 100μm; the frame material used for the cathode side sealing frame is polyethylene naphthalate PEN with a thickness of 100μm; the thickness of the perfluorosulfonic acid proton exchange membrane is 25μm; during the hot pressing assembly process, the hot pressing pressure used is 10kg / cm 2, the hot pressing temperature is 100℃.
[0039] Comparative Example 1
[0040] S1. A perfluorosulfonic acid resin solution with a mass concentration of 5wt% and a Pt / C catalyst with a Pt content of 50% were uniformly dispersed in a mass ratio of 7:1 to prepare an anode catalyst slurry. The anode catalyst slurry was then coated on one side of a 15μm perfluorosulfonic acid proton exchange membrane by ultrasonic spraying. After drying, a proton exchange membrane with an anode catalyst layer was obtained. The noble metal loading was 0.2mg / cm 2 ;
[0041] S2, a perfluorosulfonic acid resin solution with a mass concentration of 5wt% and a Pt / C catalyst with a Pt content of 60% are uniformly dispersed in a mass ratio of 5:1 to prepare a cathode catalyst slurry, and then the cathode catalyst slurry is coated on the other side of the perfluorosulfonic acid proton exchange membrane with an anode catalyst layer obtained in the above step S1 by ultrasonic spraying, and the cathode catalyst layer is coated after drying to obtain a catalyst coating proton membrane CCM, and the total precious metal loading is 0.5mg / cm 2 ;
[0042] S3. Stack the anode side gas diffusion layer, anode side sealing frame, anode catalyst layer, perfluorosulfonic acid proton exchange membrane, cathode catalyst layer, cathode side sealing frame, and cathode side gas diffusion layer in order, and then prepare a seven-in-one membrane electrode assembly by hot pressing. Among them, the thickness of the anode side gas diffusion layer is 250μm, and the material is carbon fiber cloth; the thickness of the cathode side gas diffusion layer is 250μm, and the material is carbon fiber cloth; the frame material used for the anode side sealing frame is polyethylene terephthalate PET with a thickness of 75μm; the frame material used for the cathode side sealing frame is polyethylene terephthalate PET with a thickness of 75μm; the thickness of the perfluorosulfonic acid proton exchange membrane is 15μm; during the hot pressing assembly process, the hot pressing pressure used is 20kg / cm 2 , the hot pressing temperature is 80℃.
[0043] Comparative Example 2
[0044] S1. A perfluorosulfonic acid resin solution with a mass concentration of 20wt% and a Pt / C catalyst with a Pt content of 40% were uniformly dispersed in a mass ratio of 7:1 to prepare an anode catalyst slurry. The anode catalyst slurry was then coated on one side of a 25μm perfluorosulfonic acid proton exchange membrane by ultrasonic spraying. After drying, a proton exchange membrane with an anode catalyst layer was obtained. The noble metal loading was 0.2mg / cm 2 ;
[0045] S2, a perfluorosulfonic acid resin solution with a mass concentration of 20wt% and a PtCo / C catalyst with a Pt content of 50% are evenly dispersed in a mass ratio of 2.4:1.1 to prepare a cathode catalyst slurry, and then the cathode catalyst slurry is coated on the other side of the perfluorosulfonic acid proton exchange membrane with an anode catalyst layer obtained in the above step S1 by ultrasonic spraying, and the cathode catalyst layer is coated after drying to obtain a catalyst coating proton membrane CCM, and the total precious metal loading is 0.5mg / cm 2 ;
[0046] S3. Stack the anode side gas diffusion layer, anode side sealing frame, anode catalyst layer, perfluorosulfonic acid proton exchange membrane, cathode catalyst layer, cathode side sealing frame, and cathode side gas diffusion layer in order, and then prepare a seven-in-one membrane electrode assembly by hot pressing. Among them, the thickness of the anode side gas diffusion layer is 280μm, and the material is carbon fiber paper; the thickness of the cathode side gas diffusion layer is 280m, and the material is carbon fiber paper; the frame material used for the anode side sealing frame is polyethylene naphthalate PEN with a thickness of 100μm; the frame material used for the cathode side sealing frame is polyethylene naphthalate PEN with a thickness of 100μm; the thickness of the perfluorosulfonic acid proton exchange membrane is 25μm; during the hot pressing assembly process, the hot pressing pressure used is 10kg / cm 2 , the hot pressing temperature is 100℃.
[0047] The air-cooled fuel cell stacks prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to performance tests:
[0048] The fuel cell stack includes a lower end plate, an upper end plate, a fastening rod, a seal and 40 fuel cell basic units; the lower end plate and the upper end plate are supported and connected by fastening rods, all the fuel cell basic units are located in the space between the lower end plate and the upper end plate, and seals made of fluororubber are embedded between each fuel cell basic unit. The 40 fuel cell basic units are stacked in series; a current collecting plate for collecting stack current is also provided at both ends of the 40 fuel cell basic units, and an insulating layer is provided between the current collecting plate and the upper and lower end plates.
[0049] The basic unit of a fuel cell consists of a bipolar plate and a membrane electrode assembly; the bipolar plate includes an anode plate that provides a hydrogen flow channel and a cathode plate that provides an oxygen flow channel, is 3mm thick, and is made of graphite.
[0050] (1) Test conditions: The value of the solenoid valve pressure gauge is adjusted by adjusting the hydrogen pressure reducing valve. The solenoid valve pressure gauge is set to 0.06 MPa. The hydrogen supply is controlled by switching the solenoid valve on and off. The cathode air supply flow is adjusted by controlling the fan speed. Test environment temperature: 25°C; Test environment humidity: 50%.
[0051] (2) Under the same test conditions as above, the performance of the air-cooled fuel cell stacks prepared in Examples 1 to 4 and Comparative Examples 1 to 2 was tested, and the test results are shown in Table 1. The power unit is W; the voltage unit is V; and the current unit is A.
[0052] Table 1 Test results
[0053]
[0054] It can be seen from the test results of Examples 1 to 4 and Comparative Examples 1 to 2 in Table 1 that, compared with Comparative Examples 1 to 2, the stacks described in Examples 1 to 4 have a smaller difference in power generation when the fan speed is increased or decreased; compared with Comparative Example 1, the power generation performance of the stack obtained in Example 1 has been significantly improved. This is because in the air-cooled fuel cell system, the amount of air required for the electrochemical reaction inside the fuel cell and the temperature stability in the fuel cell stack are both provided by the fan, so the supply of oxygen in the oxidant gas of each individual fuel cell cannot be controlled separately, resulting in the inability to ensure the humidity of the reaction zone inside the fuel cell. Too low or too high humidity will lead to a decrease in the power generation efficiency of the fuel cell. In the present invention, a porous material that can adjust the humidity is added to the cathode catalyst layer of the membrane electrode assembly used in the stack to achieve controllable humidity in the reaction zone inside the fuel cell. When the humidity of the catalyst layer is too high, the pores of the material can undergo capillary condensation, thereby absorbing excess water, thereby reducing the mass transfer resistance; when the humidity of the catalyst layer is too low, the water stored in the pores of the material is released through the pores, thereby increasing the moisture content of the catalyst layer and improving the power generation efficiency of the fuel cell. Moreover, due to the introduction of porous materials, the three-phase reaction interface of the catalyst layer is enlarged, and the utilization efficiency of the oxidant oxygen is improved.
Claims
1. A membrane electrode assembly for an air-cooled fuel cell, characterized in that: The membrane electrode assembly has a seven-in-one structure, which is stacked in the order of anode side gas diffusion layer, anode side sealing frame, anode catalyst layer, perfluorosulfonic acid proton exchange membrane, cathode catalyst layer, cathode side sealing frame, and cathode side gas diffusion layer.
2. The membrane electrode assembly of an air-cooled fuel cell according to claim 1, characterized in that: The thickness of the anode side gas diffusion layer is 250-340 μm, and the anode side gas diffusion layer is a kind of carbon fiber paper or carbon fiber cloth; the thickness of the cathode side gas diffusion layer is 250-340 μm, and the cathode side gas diffusion layer is a kind of carbon fiber paper or carbon fiber cloth; the thickness of the perfluorosulfonic acid proton exchange membrane is 15-25 μm.
3. The membrane electrode assembly of an air-cooled fuel cell according to claim 1, characterized in that: The anode catalyst layer is obtained by uniformly dispersing a perfluorosulfonic acid resin solution and a noble metal catalyst to form an anode catalyst slurry, and then coating it on one side of a perfluorosulfonic acid proton exchange membrane by ultrasonic spraying.
4. The membrane electrode assembly of an air-cooled fuel cell according to claim 3, characterized in that: The mass concentration of the perfluorosulfonic acid resin solution is 5-20wt%; the type of the noble metal catalyst is one of Pt / C catalyst, PtCo / C catalyst or PtIr / C catalyst, the mass ratio of the perfluorosulfonic acid resin solution to the noble metal catalyst is 1-10:1; the noble metal loading in the anode catalyst layer is 0.1-0.2mg / cm 2 .
5. The membrane electrode assembly of an air-cooled fuel cell according to claim 1, characterized in that: The cathode catalyst layer is obtained by uniformly dispersing a perfluorosulfonic acid resin solution, a noble metal catalyst and a porous material to form a cathode catalyst slurry, and then coating the slurry on the other side of a perfluorosulfonic acid proton exchange membrane by ultrasonic spraying.
6. The membrane electrode assembly of an air-cooled fuel cell according to claim 5, characterized in that: The mass concentration of the perfluorosulfonic acid resin solution is 5-20wt%; the type of the noble metal catalyst is one of Pt / C, PtCo / C or PtNi / C catalysts; the mass ratio of the perfluorosulfonic acid resin solution to the noble metal catalyst is 1-8:1; the noble metal loading in the cathode catalyst layer is 0.1-0.5mg / cm 2 The porous material is one or a mixture of two or more of porous ceramic materials, metal organic framework materials, mesoporous porous silica, three-dimensional porous carbon nanotubes and polymer porous materials, and the mass of the porous material accounts for 0.7 to 3% of the total mass of the cathode catalyst slurry.
7. The membrane electrode assembly of an air-cooled fuel cell according to claim 1, characterized in that: The thickness of the frame material used for the anode side sealing frame and the cathode side sealing frame is 50-100 μm, and the frame material is one of polyethylene terephthalate PET, polyethylene naphthalate PEN, polyimide PI or polyetherimide PEI.
8. The method for preparing a membrane electrode assembly of an air-cooled fuel cell according to any one of claims 1 to 7, characterized in that: The membrane electrode assembly is assembled by hot pressing.
9. The method for preparing a membrane electrode assembly of an air-cooled fuel cell according to claim 8, characterized in that: Hot pressing pressure is 10-25kg / cm 2 , the hot pressing temperature is 80-110℃.
10. An air-cooled fuel cell stack, characterized in that: The fuel cell stack is assembled using a membrane electrode assembly of an air-cooled fuel cell as described in any one of claims 1-7.